Genetic and phenotypic relationships among Pinus sylvestris populations in the Pieniny National Park - Urbaniak, Lech; Lesiczka, Paulina; Gąsiorowska, Ewa; Pawlaczyk, Ewa M.; Androsiuk, Piotr; Lewandowska-Wosik, Anetta; Vončina, Grzegorz (Archives of Biological Sciences, 2018)
The phenotypic and genetic relationships among five Pinus sylvestris populations in the western part of the Carpathian Mountains were analyzed based on seven morphological needle traits and 67 loci using 10 RAPD primers. Three of the studied populations were on the western side (Macelowa Góra, Czubatka, Łazowa Skałka) and two were located in the central part (Sokolica, Zamkowa Góra) of the Pieniny National Park. The examined populations had short needles, which is characteristic for mountain habitats of the Scots pine. The populations from the Pieniny Mts. had fewer rows of stomata on both sides of the needles than others studied stands of Eurosiberian Scots pine. The number of stomata on both flat and convex sides of the needles was similar to the values observed for populations growing on the nearby Tatra Mountains. Moreover, when these two traits are considered, the populations from Sokolica and Łazowa Skałka share the highest degree of similarity.. Nei’s genetic distances and genetic identities between the populations were calculated on the basis of RAPD loci. The results show that the lowest Nei’s distance exists between the populations from the western part of the Pieniny Mts. – Macelowa Góra and Czubatka, and its central part – Sokolica and Zamkowa Góra, with the highest values recorded between the populations of Zamkowa Góra and Czubatka, and Łazowa Skałka and Czubatka. A similar pattern of phenotypic and genetic relations that was observed between the populations in both regions of the Pieniny Mountains could be the result of planting-seed material sourced from the central Pieniny Mts. in the area of western Pieniny Mts. https://doi.org/10.2298/ABS170525045U Received: May 25, 2017; Revised: October 23, 2017; Accepted: October 23, 2017; Published online: November 27, 2017 How to cite this article: Urbaniak L, Lesiczka P, Gąsiorowska E, Pawlaczyk EM, Androsiuk P, Lewandowska-Wosik A, Vončina G. Genetic and phenotypic relationships among Pinus sylvestris populations in the Pieniny National Park. Arch Biol Sci. 2018;70(2):289-97.